It's hard to meet nutrition goals if you don't have data on nutrition - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
At a 2012 meeting of the World Health Assembly, all 193 UN member nations committed to achieving global nutrition targets by 2025. So far, the number of countries on course to meet the global targets is much too low. This is complicated by the fact that too many countries lack the data necessary to even evaluate their nutrition progress against the global targets.